THE MANY SIDES OF A COIN: EXPLORING THE COST AND VALUE OF TOKENS IN CHATURBATE - Hernandez, Antonia (AoIR Selected Papers of Internet Research, 2020)
On the sexcam platform Chaturbate.com, a ‘token’ is at the same time the name of a unit of made-up currency (‘tokens’) and its descriptor (something issued by an authority that can be exchanged later on). A token stands in for something else. But what else, exactly? As this paper develops, Chaturbate tokens have different uses and meanings for the audience and performers. These differences do not only happen at the users’ level but are sustained by an ecology of associated payment services that deepen the contrast between them. An analysis of the differences in cost and value of tokens, and the environment in which these dissimilarities occur, illustrates the role of tokens as an extractive technology that profits from, and perpetuates, financial discrimination.